Design and development of Ultra Wideband (UWB) wireless transmission using Simulink - S.Sharmila A/P Sambasivam (Universiti Malaysia Perlis, 2008)
Ultra-wideband (UWB) technology is ideal for portable multimedia devices because of its inherent low power consumption, short range, high data rates of up to 480 Mbps and large spatial capacity. Furthermore, the power is low enough to prevent interference with other wireless services. This new standard has recently been approved by the Federal Communication Commision (FCC) for unlicensed use and has been gaining interest throughout the consumer electronics industry. This emerging technology provides the high bandwidth that multiple digital video and audio streams require throughout the home. With the support of industry, like Intel, UWB technology promises to make it easy to create highspeed Wireless Personal Area Networks (WPAN) that can connect devices throughout the home. The main goal of the project is to increase interest in UWB technology and to explore its usefulness. The history and benefits of UWB will be discussed, followed by the project objectives and implementation. A model will be created in Matlab/Simulink to understand the various components required for transmitting and receiving. A simple UWB transmitter model and receiver model are designed according to its requirements. To transmit and receive the signal an AWGN channel model is designed. The transmitted spectrum spans should be approximately 500 MHz. The center frequency of this signal is 3.432 GHz. Finally, it can be concluded that only a part of objective of this project is achieved.